Kepastian Hukum Terhadap Perlindungan Pekerja Dengan Perjanjian Pemborongan - Muhamad Ali; Muh Nasir; Junaedi (KRAKATAU (Indonesian of Multidisciplinary Journals), 2024)
Humans must work to fulfill their needs. To do this work, individuals enter into an employment relationship with an employer. The employment relationship can be established based on a contract. Whether it is a fixed-term employment contract or a temporary employment contract, there are also contracts made as part of an employment contract. Workers who work under contract agreements are also workers who need certainty of legal protection in order to realize the right to work that is decent for humanity. Changes to the provisions of contracts that have been completed by Law Number 13 of 2003 concerning Manpower after Law Number 6 of 2023 concerning State Regulations, and not Law Number 2 of 2022 concerning Manpower Law which became law, caused a lot of controversy. Using the normative juridical research method, the author will examine the extent to which this regulatory change creates legal certainty in protecting the rights of workers employed under an agreed contract. Based on research into the law, the author concludes that this latest law is likely to cause harm to employees whose status is a contractual agreement, hereinafter referred to as outsourcing. Therefore, according to the author, additional regulations are needed that contain detailed rules ranging from implementation requirements to sanctions against employers who violate the Regulation on the rights of workers through subcontracting or outsourcing contracts.